RISK MANAGEMENT ANALYSIS RELATED TO THE ROLE OF INDEPENDENT QUALITY CONTROL CONSULTANTS (PMI) IN THE TRANSITION OF FUNDING FROM TOLL ROAD BUSINESS ENTITIES (BUJT) TO THE STATE BUDGET (APBN) IN TOLL ROAD INFRASTRUCTURE PROJECTS USING THE SEM-PLS AND ANALYTICAL HIERARCHY PROCESS METHODS - Muhammad Rifki Rahman; Erry Rimawan; Mawardi Amin (RADJA PUBLIKA, 2026)
This study analyzes risk management related to the role of Independent Quality Control Consultants during the transition of toll road infrastructure project funding from Toll Road Business Entities (BUJT) to the State Budget (APBN). The funding transition introduces complex regulatory, technical, and coordination challenges that may affect project quality, time performance, and compliance. Therefore, this research aims to examine the influence of competence and risk assessment on the effectiveness of PMI performance, with stakeholder management positioned as an intervening variable. A mixed analytical approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and the Analytical Hierarchy Process (AHP). SEM-PLS was applied to test causal relationships among variables, while AHP was used to determine the priority level of factors influencing PMI effectiveness. Data were collected from professionals involved in toll road infrastructure projects, including consultants, contractors, supervisors, and academics. The results show that competence and risk assessment have a significant positive effect on the effectiveness of PMI performance. Furthermore, stakeholder management significantly mediates the relationship between competence and performance, as well as between risk assessment and performance, indicating that effective communication, coordination, and collaboration enhance the impact of technical capabilities and risk control. The AHP analysis reveals that the implementation of government regulatory standards is the most influential factor, followed by professional independence, ethical integrity, and human resource competence in understanding public funding regulations. In conclusion, the effectiveness of PMI during the BUJT-to-APBN funding transition depends on an integrated approach that combines regulatory compliance, professional competence, structured risk assessment, and stakeholder management. These findings provide strategic insights for policymakers and practitioners in strengthening quality control systems within toll road infrastructure projects.